Best Management Practices in the Everglades Agricultural Area: Soil Testing - Samira H. Daroub; Orlando A. Diaz; Timothy A. Lang; Ming Chen (EDIS)
The purpose of this document is to outline the process of soil testing as an important tool for both fertilizer recommendations and as a BMP in this region. This EDIS article is one in a series which attempts to explain in easily understandable terms the implementation methods and rationale behind the main P load reducing BMPs employed on EAA farms. This document is Fact Sheet SL-225, one of a series of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 2005.